2021
DOI: 10.1073/pnas.2026046118
|View full text |Cite
|
Sign up to set email alerts
|

Economic games can be used to promote cooperation in the field

Abstract: We present experimental evidence of the impact of playing a game on real-life cooperation. The game was framed as a pest-management activity, the effectiveness of which depends on the decisions of others. Playing the game changes behavior in the field, increasing the participation in all collective activities directed at reducing pest pressure. The economic impact of those activities is important, leading to losses that are ∼20% lower than in the control group. Increased cooperation reflects changes in the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The promotion of the agricultural sector could potentially act as a crucial instrument for augmenting inclusive economic growth [15].…”
Section: South Africamentioning
confidence: 99%
“…The promotion of the agricultural sector could potentially act as a crucial instrument for augmenting inclusive economic growth [15].…”
Section: South Africamentioning
confidence: 99%
“…An emerging body of literature explores the use of group dynamic games as an intervention tool to facilitate sustainable commons management (Becu et al 2017, Craven et al 2017, Ferrero et al 2018, Meyer et al 2021, Bartels et al 2022 because they provide participants with useful metaphors for their daily lives Carpenter 2008, Meinzen-Dick et al 2018). Approaches cover role-playing games (Barreteau et al 2001, Bousquet et al 2002 as well as behavioral games used in experimental economics Carpenter 2008, Janssen et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…1 These games are structured spaces where players can acquire knowledge by experiencing, re ecting, and experimenting, which leads to improved understanding and enhanced problem-solving capacities for participants. [1][2][3][4] Economic games, in particular, focus on the key underlying social dilemmas, while also being a rather low-cost and scalable intervention. 5 While games are an increasingly common intervention tool, their impacts on real-life behavioral change have not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…5 While games are an increasingly common intervention tool, their impacts on real-life behavioral change have not been well documented. 4 However, a few recent studies observed signi cant effects on collective action when compared with a control group without the game intervention. 3,4,6 For the study discussed here, we conducted economic games with users of rainfed dams in 56 randomly selected villages in Madhya Pradesh, India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation